Cardiorespiratory fitness, obesity and left atrial function in patients with atrial fibrillation. (October 2022) - Mishima, Ricardo S.; Ariyaratnam, Jonathan P.; Pitman, Bradley M.; Malik, Varun; Emami, Mehrdad; McNamee, Olivia; Stokes, Michael B.; Lau, Dennis H.; Sanders, Prashanthan; Elliott, Adrian D.
Abstract: Background: Low cardiorespiratory fitness (CRF) and obesity are related to the development and maintenance of atrial fibrillation (AF). The aim of this study was to determine the association between CRF, obesity and left atrial (LA) mechanical parameters in patients with AF. Methods: A cohort of 154 consecutive paroxysmal and persistent AF patients (Age: 62 ± 10, 26% female) referred for exercise stress testing and transthoracic echocardiography were included. We included patients in sinus rhythm with preserved left ventricular ejection fraction who were able to complete a maximal exercise test. Left atrial strain in the reservoir (LASr), booster (LASb) and conduit (LASc) phases were assessed using dedicated software. LA stiffness, emptying fraction (LAEF) and LA to LV ratio were calculated using previously described formulas. Results: CRF was positively associated with LAEF (β = 1.3, 95% CI 0.1–2.3, p = 0.02), reservoir (β = 1.5, 95% CI 0.9–2.1, p < 0.001), booster (β = 0.8, 95% CI 0.4–1.2, p < 0.001) and conduit strain (β = 0.7, 95% CI 0.3–1.1, p = 0.001). We observed an inverse association between CRF and both LA stiffness index (β = −0.02, 95% CI (−0.03)–(−0.01), p < 0.001) and LA to LV ratio (β = −0.03, 95% CI (−0.04)–(−0.01), p < 0.001). Obese patients had significantly higher indexed LA volumes compared to overweight and normal BMI patients. The association between obesity and measures of LA function and stiffness did not reach statistical significance. Conclusion: Among AF patients, higher CRF was independently associated with greater LA function and compliance. Obesity was associated with higher LA volumes yet preserved mechanical function.